1995
DOI: 10.1007/bf00346878
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of intrasplenically transplanted adult hepatocytes and fetal liver in hyperbilirubinemic Gunn rats

Abstract: We performed adult hepatocyte transplantation (HCTx) and fetal liver transplantation (FLTx) into the spleens of hyperbilirubinemic Gunn rats in congenic combination and we compared the long-term effects of these procedures for as long as 12 months. Proliferative activity of intrasplenic hepatocytes was evaluated using antiproliferating cell nuclear antigen (PCNA) immunohistochemical staining. The serum total bilirubin levels (T. Bil) significantly decreased from 7.16 +/- 0.25 mg/dl to 4.38 +/- 0.60 mg/dl 2 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Although the use of adult cells has been studied in depth, there have been few reports on the effect of fetal liver transplantation. Fetal liver cells are highly regenerative and are known to grow and function for a long period after intrasplenic transplantation [13,14] as we have seen in our previous work [15]. Thus, in the present study, we performed fetal and adult intrasplenic hepatocyte transplantation in hyperbilirubinemic Gunn rats, bearing a defect in the bilirubin-UDP-glucuronosyl transferase gene, leading to accumulation of unconjugated bilirubin in the serum, similar to Crigler-Najjar type I syndrome in humans.…”
Section: Introductionsupporting
confidence: 51%
“…Although the use of adult cells has been studied in depth, there have been few reports on the effect of fetal liver transplantation. Fetal liver cells are highly regenerative and are known to grow and function for a long period after intrasplenic transplantation [13,14] as we have seen in our previous work [15]. Thus, in the present study, we performed fetal and adult intrasplenic hepatocyte transplantation in hyperbilirubinemic Gunn rats, bearing a defect in the bilirubin-UDP-glucuronosyl transferase gene, leading to accumulation of unconjugated bilirubin in the serum, similar to Crigler-Najjar type I syndrome in humans.…”
Section: Introductionsupporting
confidence: 51%
“…In the Gunn rat model, a surrogate for human Crigler-Najjar Syndrome type 1 defect of bilirubin uridine diphosphate glucuronosyltransferase (bili UDPG transferase), 12% of the whole liver mass normalized bilirubin metabolism (41). KoKudo et al used normal, untreated, congenic rats (Wistar Shi) as sources of whole liver (for orthotopic liver transplantation [OLT]), or as donors of fetal or adult hepatocytes for transplant into Gunn rats, and studied bilirubin metabolism for 12 months (42). The intrasplenic transplanted fetal and adult congenic hepatocytes (10 7 cells, representing 2% liver mass) reduced total bilirubin by 30% at two months (compared to nl total bilirubin at two months with whole liver grafts), and at four months the hepatocytes expressed bilirubin glucuronide fractions 28 to 36% of total biliru- bin (compared to nl bilirubin glucuronide fractions with whole liver grafts at four months) (42).…”
Section: Hepatocyte Transplantation For Metabolic Liver Diseasementioning
confidence: 99%
“…KoKudo et al used normal, untreated, congenic rats (Wistar Shi) as sources of whole liver (for orthotopic liver transplantation [OLT]), or as donors of fetal or adult hepatocytes for transplant into Gunn rats, and studied bilirubin metabolism for 12 months (42). The intrasplenic transplanted fetal and adult congenic hepatocytes (10 7 cells, representing 2% liver mass) reduced total bilirubin by 30% at two months (compared to nl total bilirubin at two months with whole liver grafts), and at four months the hepatocytes expressed bilirubin glucuronide fractions 28 to 36% of total biliru- bin (compared to nl bilirubin glucuronide fractions with whole liver grafts at four months) (42). Colocalization studies of adenosine triphosphate and dipeptidyl peptidase IV (to illustrate gap junctions) of hepatocytes transplanted into the spleens of rats deficient in dipeptidyl peptidase IV, activity found that the transplanted hepatocytes rapidly overcame structural barriers, entered liver plates, and even formed chimeric bile canaliculi (43).…”
Section: Hepatocyte Transplantation For Metabolic Liver Diseasementioning
confidence: 99%
“…These improvements were noticed after foetal hepatocyte transplantation into RS-pre-treated Gunn rats (FHT-RS) two weeks after the treatment and lasted throughout the experimental period. Furthermore, after FHT the decrease in TSB is more remarkable from 3 months on after transplantation (Kokudo et al 1995a). When, T 3 was administered in RS-pre-treated animals both foetal and adult cells transplantation resulted in an improvement of TSB at all times of the study.…”
Section: Discussionmentioning
confidence: 98%
“…There have been several reports on the functionality of hepatocytes after transplantation in Gunn rats (Kokudo et al 1995a;Cubero et al 2001). These improvements were noticed after foetal hepatocyte transplantation into RS-pre-treated Gunn rats (FHT-RS) two weeks after the treatment and lasted throughout the experimental period.…”
Section: Discussionmentioning
confidence: 99%